Analysis Of The Marketing Mix On Consumer Purchasing Decisions At PO Primadona Makassar - Eben Haezer Basran Patandean; Herna Sulle Tondon (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study aims to empirically analyze and test the influence of the elements of the Service Marketing Mix (7Ps), which include Product, Price, Place, Promotion, People, Process, and Physical Evidence, on Consumer Purchasing Decisions at the Primadona bus company (PO Primadona) in Makassar. Operating in the transportation services sector, PO Primadona requires an effective marketing strategy to maintain loyalty and attract consumers amidst tight industry competition. This research employs a quantitative approach with a causal explanatory design. Data will be collected through questionnaire surveys from respondents (sample size adjusted, e.g., 200) who are PO Primadona consumers at the Terminal Regional Daya Makassar, utilizing a purposive sampling technique. Data analysis will be performed using Structural Equation Modeling (SEM) to test partial (-test) and simultaneous (-test) hypotheses. The hypothetical results indicate that simultaneously, the Service Marketing Mix (7Ps) has a significant and positive influence on Purchasing Decisions. Partially, the variables Product Quality (Service) (e.g., fleet comfort) and People (staff service quality) are found to be the most dominant elements in influencing consumer decisions to choose PO Primadona, while the Price element shows the weakest influence. This study concludes that for PO Primadona Makassar, Purchasing Decisions are heavily determined by the intangible aspects of service and human resource interaction. services. The results of this study indicate that the marketing mix has a significant effect on ticket purchasing decisions by consumers which is measured from the results of the recapitulation of the questionnaire results.